2013
DOI: 10.1113/jphysiol.2013.256875
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of synaptic depression of the calyx of Held synapse by GABAB receptors and spontaneous activity

Abstract: Key points• Spontaneous activity contributes to low synaptic depression of the calyx of Held synapse in vivo.• Application of a reversible blocker in combination with juxtacellular recordings allows a relatively good estimate of local drug concentrations reached during microiontophoresis.• Activation of the GABA B receptor on the young-adult calyx of Held can reduce short-term depression, both in vivo and in slices.• The ambient concentration of GABA in the auditory brainstem is low. AbstractThe calyx of Held … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 95 publications
3
16
0
Order By: Relevance
“…Spontaneous firing rates in this study were lower than in our earlier study in the C57BL/6 background ( Lorteije et al, 2009 ), but similar as in other studies in both mice and other species ( Kopp-Scheinpflug et al, 2008 ; Wang et al, 2013 ). Synaptic transmission along the calyx of Held synapse in the WT animals generally matched our previous in vivo experiments as well, including the observation that STD during a tone was lower in the studies in which spontaneous frequency was higher, presumably because of larger tonic depression ( Lorteije et al, 2009 ; Wang et al, 2013 ).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Spontaneous firing rates in this study were lower than in our earlier study in the C57BL/6 background ( Lorteije et al, 2009 ), but similar as in other studies in both mice and other species ( Kopp-Scheinpflug et al, 2008 ; Wang et al, 2013 ). Synaptic transmission along the calyx of Held synapse in the WT animals generally matched our previous in vivo experiments as well, including the observation that STD during a tone was lower in the studies in which spontaneous frequency was higher, presumably because of larger tonic depression ( Lorteije et al, 2009 ; Wang et al, 2013 ).…”
Section: Discussionsupporting
confidence: 86%
“…Similarly, the peak of the eAP, which typically coincides with the maximum rate of rise of the postsynaptic AP, provides a measure for the postsynaptic excitability. Because of the difficulty of delineating the amplitude of the eEPSP from the eAP, we used the eEPSP’ as a measure for the strength of transmission, as previously described ( Wang et al, 2013 ). The absolute size of the eEPSP’ depends on experimental parameters such as seal resistance; on average it was about 10 V/s; this value did not differ significantly between mutant and its WT control for any of the four lines (Supplementary Figure S5 ).…”
Section: Methodsmentioning
confidence: 99%
“…2011; Wang et al . ), perhaps including the LC neurons, as our EM study showed presynaptic location of GABA B Rs in the LC. As GABA B R signalling and the activity of GABA transporters in many physiological and pathological processes can be regulated by various transmitter/receptor systems, such as the activation of 5‐HT 1A receptors during chronic exposure to SSRIs, our results suggest that tonic inhibition and presynaptic regulation of transmitter release mediated by peri/extrasynaptic GABA B Rs on LC neurons could be important players in the development of normal and abnormal behaviours/brain functions that are associated with the LC–NA system.…”
Section: Discussionmentioning
confidence: 59%
“…For example, since ambient GABA levels in the LC are significantly higher during REM/non-REM sleep than during wakefulness (Nitz & Siegel, 1997;Nelson et al 2002), our results suggest that GABA B R-mediated tonic inhibition may play an important role in regulating the SFR of LC neurons, and thus the wakefulness/arousal level of the brain. In addition to postsynaptic regulation, GABA B Rs at presynaptic sites have been shown to regulate glutamate and GABA release in many brain areas (Wu et al 2011;Wang et al 2013), perhaps including the LC neurons, as our EM study showed presynaptic location of GABA B Rs in the LC. As GABA B R signalling and the activity of GABA transporters in many physiological and pathological processes can be regulated by various transmitter/receptor systems, such as the activation of 5-HT 1A receptors during chronic exposure to SSRIs, our results suggest that tonic inhibition and presynaptic regulation of transmitter release mediated by peri/extrasynaptic GABA B Rs on LC neurons could be important players in the development of normal and abnormal behaviours/brain functions that are associated with the LC-NA system.…”
mentioning
confidence: 55%
“…At the same time, these authors found that release probability time is not assumed to be constant any longer (assumption 2, above) but is calculated as the product of a fixed rate-constant and the number of empty release sites. In other words: pool refilling is assumed to start only after some delay, when sites have been vacated (Hosoi et al, 2007;Thanawala and Regehr, 2013;Wang et al, 2013;Wesseling and Lo, 2002). Thanawala and Regehr (2013) simulated this type of model and concluded that the simple back-extrapolation (SMN plot) underestimates the real pool, because it assigns too much of the early release to newly recruited vesicles.…”
Section: Correction For Incomplete Pool Depletionmentioning
confidence: 99%